Gambaran Karakteristik dan Pengetahuan Kader Posyandu dalam Pengukuran Antropometri Di Wilayah Puskesmas Gedung Meneng, Kabupaten Tulang Bawang 2024 - Anggun Rusyantia; Sefanadia Putri; Mara Sari Arsyad Temenggung (Nutrition Department, Poltekkes Kemenkes Tanjung Karang, 2025)
Integrated Health Service Posts (Posyandu) are community-based health efforts managed by cadres to provide easy access to basic health services, including anthropometric measurements of toddlers. The characteristics and roles of cadres influence the monitoring of toddler growth and development. This study aims to assess the characteristics, knowledge, and skills of Posyandu cadres in performing anthropometric measurements of toddlers at the Gedung Meneng Community Health Center, Tulang Bawang Regency. This research uses a quantitative descriptive approach with a sample of 46 cadres from the Gedung Meneng Community Health Center area. The results showed that the average age of the cadres is 41 years, with most having completed elementary school (45.7%), junior high school (28.3%), and high school (26.1%). All cadres have more than one year of work experience. The knowledge of cadres regarding anthropometric measurements is predominantly good (80.4%), while 19.6% have moderate knowledge. In terms of skills, 52.1% of cadres are skilled in measuring infant weight, 60.9% in digital weighing, and 63% in height measurement. However, 65.2% were not skilled in measuring body length, 71.8% in measuring arm circumference, and 58.7% in measuring head circumference. Despite good knowledge, skills were not fully optimized. Therefore, it is recommended that the Gedung Meneng Community Health Center involve nutritionists to provide re-training and continuous support to improve the skills of cadres.